A non‐linear adaptive excitation control scheme for feedback linearized synchronous generations in multimachine power systems. Issue 9 (12th February 2021) - Roy, Tushar Kanti; Mahmud, Md. Apel; Shen, Weixiang; Oo, Amanullah Maung Than
Abstract: A new adaptive scheme is proposed in this paper to design excitation controllers for feedback linearized models of synchronous generators in multimachine power systems in order to ensure the stability during large disturbances. The proposed scheme uses speed deviations of synchronous generators, readily available measured physical properties of multimachine power systems, to make all generators within a power network as partially linearized as well as to provide more damping. An adaptive scheme is then used to estimate all unknown parameters which appear in the partial feedback linearizing excitation controllers in order to avoid parameter sensitivities of existing feedback linearization techniques. The overall stability of multimachine power systems is ensured through the excitation control and parameter adaptation laws. The Lyapunov stability theory is used to theoretically analyse the stability of multimachine power systems with the proposed scheme. Simulation studies are presented to evaluate the performance of the proposed excitation control scheme for two different test systems by different operating conditions including short‐circuit faults on key locations along with variations in parameters for a large duration. Furthermore, comparative results are presented to highlight the superiority of the proposed adaptive partial feedback linearizing excitation control scheme over an existing partial feedback linearizing excitation controllers.